From Hidden to Highlighted: Students’ Perceptions of the PERLs Module in Undergraduate Medical Education in Pakistan - Naeem, Noor-i-Kiran; Rahim, Khalid; Minhas, Rafia; Arooj, Zartashia; Husnain Danish; Adeen Akram (Journal of University Medical & Dental College, 2026)
BACKGROUND &OBJECTIVE: In Pakistan’s undergraduate medical education context, the PERLs (Professionalism, Ethics, Research, and Leadership) module has been introduced to align with modern integrated curricula. This study aimed to explore students’ perceptions of the PERLs module and its influence on professional development and clinical practice within a private medical college in Pakistan. METHODOLOGY: A mixed-method sequential explanatory study comprised a cross-sectional survey of 78 medical students, followed by in-depth interviews of 8 participants to gain richer qualitative insights. Survey data were analyzed using descriptive statistics, while interview transcripts underwent thematic analysis. RESULTS: Survey findings demonstrated strong student agreement on the relevance and applicability of the PERLs module to medical practice, with mean ratings ranging from 4.077 to 4.462(out of 5). Students acknowledged the module’s role in preparing them for ethical challenges, enhancing clinical practice skills, and advancing professional development. Qualitative themes reinforced these outcomes, highlighting the module’s practical utility in addressing real-world ethical dilemmas, strengthening research and clinical reasoning, and cultivating teamwork, communication, and leadership. Suggestions for improvement emphasized the need for more accessible resources, expanded practical exposure, and improved time allocation within the module. CONCLUSION: Students viewed the PERLs module as an effective bridge between theory and practice, supporting their growth as competent and ethical future physicians. With targeted enhancements to resources, practical engagement, and time management, the module has strong potential to advance professional identity formation in medical education.